Pengaruh Perlakuan Pajak Terhadap Penghasilan Selebriti Instagram Dari Hasil Endorsement - Ayu Qurnia Sari Endang Setyaningsih (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2021)
This study aims to find out if the income of Selebgram from endorsement results can be taxed as well as how it is collected and to know the precept of Selebgram against the application of income tax from endorsement results. The data collection techniques used in this study are with structured interviews to dig up the necessary information. The informants selected in this study are KPP Pratama Yogyakarta, Tax Consultant in Yogyakarta, Tax Expert in Yogyakarta, and Instagram Celebrity in Yogyakarta & Central Java. The results of this study show that the income of the celebrant is an excavation of the object of the new tax and the collection is the same as the collection of other taxes. Instagram celebrities agree to be taxed but with certain transaction restrictions.